2021
DOI: 10.3390/ph14100994
|View full text |Cite
|
Sign up to set email alerts
|

Soft Coral-Derived Dihydrosinularin Exhibits Antiproliferative Effects Associated with Apoptosis and DNA Damage in Oral Cancer Cells

Abstract: Dihydrosinularin (DHS) is an analog of soft coral-derived sinularin; however, the anticancer effects and mechanisms of DHS have seldom been reported. This investigation examined the antiproliferation ability and mechanisms of DHS on oral cancer cells. In a cell viability assay, DHS showed growth inhibition against several types of oral cancer cell lines (Ca9-22, SCC-9, OECM-1, CAL 27, OC-2, and HSC-3) with no cytotoxic side effects on non-malignant oral cells (HGF-1). Ca9-22 and SCC-9 cell lines showing high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Sinularin (48) exerts oxidative stress-mediated anti-proliferative, G2/M-blocking, and apoptotic effects on OCC and is associated with ROS production, making it a potential marine drug against oral cancer [82]. Yang et al [83] confirmed that dihydrosinularin (49) exerts its anti-proliferative effect on OCC by inducing apoptosis, double-strand breaks, and DNA oxidative damage without causing cytotoxicity to non-malignant oral cells. Trichodermin (50) inhibits the migration and invasion of OSCC Ca922 and HSC-3 cells by down-regulating the expression of MMP-9.…”
Section: Terpenoids and Steroidsmentioning
confidence: 99%
“…Sinularin (48) exerts oxidative stress-mediated anti-proliferative, G2/M-blocking, and apoptotic effects on OCC and is associated with ROS production, making it a potential marine drug against oral cancer [82]. Yang et al [83] confirmed that dihydrosinularin (49) exerts its anti-proliferative effect on OCC by inducing apoptosis, double-strand breaks, and DNA oxidative damage without causing cytotoxicity to non-malignant oral cells. Trichodermin (50) inhibits the migration and invasion of OSCC Ca922 and HSC-3 cells by down-regulating the expression of MMP-9.…”
Section: Terpenoids and Steroidsmentioning
confidence: 99%
“…In this study, DHS was first time reported to possess antiproliferative activity against cancer cells with no toxicity on noncancerous cells. [68] Gastropods are a class of invertebrates from the phylum Mollusca. 1).…”
Section: Zhang Et Al Isolated Compounds Varioloid a And Varioloid B Frommentioning
confidence: 99%
“…[150] (4) The other mechanisms such as DNA damage due to some genetic changes, cell death inhibition using proapoptotic markers, or drug inactivation by various metabolic changes cause the drug to accumulate inside the cells to induce cytotoxic activity. [68] Recent research has shown that using targeted nanomedicines to deliver treatments directly to tumor cells can be an efficient strategy with reduced side effects of anticancer medications. [163] Three different natural sources of lecithin were used to make chitosancoated nanoliposomes containing CUR.…”
Section: Nanotechnology Approach Applied To Marine Agents For Overcom...mentioning
confidence: 99%
“…Three types of oxidative stress biomarkers were assessed, including ROS, MitoSOX, and MMP. According to the user's manual, their matched probes, such as 2 ,7 -dichlorodihydrofluorescein diacetate (H 2 DCFDA) [46] (Sigma-Aldrich), MitoSOX™ Red [47] (Thermo Fisher Scientific, Carlsbad, CA, USA), and DiOC 2 (3) (Invitrogen, San Diego, CA, USA) [48], were chosen to detect the ROS, MitoSOX, and MMP, respectively. After the oxidative stress reaction, these probes become fluorescent molecules.…”
Section: Oxidative Stressmentioning
confidence: 99%